The Protective Effect of Vitamin E for Reducing Intra-Hospital Mortality in Acute Limb Ischemia Patients - Suci Indriani; Suko Adiarto; Hananto Andriantoro; Ismoyo Sunu; Taofan Siddiq; Iwan Dakota (Jurnal Kardiologi Indonesia, 2021)
Background Management of acute limb ischemia (ALI) is still a huge challenge. Current advances of endovascular therapeutic approach in management of ALI have decreased the overall amputation rate, nevertheless, mortality rate remains high which may be caused by metabolic consequences of reperfusion injury. Aim To understand the role of vitamin E to intra-hospital and 30-day mortality among acute limb ischemia patients. Methods This retrospective cohort study included all patients with ALI between 2015 to 2018. Vitamin E 2x400 mg orally for seven days was given based on physician preference after ALI diagnosis was confirmed. Data were collected from Vascular Registries of National Cardiovascular Center Harapan Kita (NCCHK), Jakarta, Indonesia. Univariate analysis and logistic regression models were used to explore factors that contribute to intra-hospital and 30-day mortality. Results A total of 160 patients with ALI involving 192 limbs were admitted to our hospital. Mostly were male (63.1%) and mean age were 56±13 years old. Majority of the patients had unilateral lesion (80%), and were diagnosed with Rutherford stage IIA (36.3%), followed by stage IIB (33.8%), stage I (20%), and stage III (10%) respectively. Intra-hospital and 30-day mortality were 28.1% and 36.9%, respectively. Low treatment of vitamin E increased intra-hospital mortality (HR 5,6 95%CI 1.7-18.3), however, it did not affect 30-day mortality. Other factors including IABP insertion, arrhythmia, bleeding requiring transfusion and acute renal failure were associated with higher intra-hospital and 30-day mortality. In addition, menopause (HR 3.2; CI 1.16-8.85) was also a predictor of 30-day mortality. Conclusion Vitamin E administration reduced intra-hospital mortality but not on 30-day mortality in acute limb ischemia patients. Keywords: Acute Limb Ischemia, vitamin E, mortality, reperfusion injury